2012
DOI: 10.1186/1477-7819-10-102
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic activity in Libyan breast cancer

Abstract: BackgroundWe evaluated the relationship of the apoptotic activity index (AI) and the standardized mitotic-apoptotic ratio (SMI/AI) with clinicopathological features and prognosis in Libyan female breast cancer (BC) patients. We then compared our results with corresponding results in Finnish and Nigerian female BC patients.MethodsHistological samples of breast carcinoma from 130 patients were retrospectively studied: an estimation of the apoptotic activity per square millimeter (expressed as apoptotic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Nonetheless, it is worth noteworthy that our results are in agreement with those presented by some other authors [10], who have demonstrated statistical trend (but not significance) towards higher apoptosis in pathological responders after neoadjuvant chemotherapy based on ATC (see Table 1). On the other hand, some researchers have shown significant correlation between low AI and better treatment outcome of BC patients [8,11]. Their results are also slightly similar to those presented by us, because in our analysis, the subgroup of women with quite good prognosis (DFS = 84.6 %) was characterized by the lowest AI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nonetheless, it is worth noteworthy that our results are in agreement with those presented by some other authors [10], who have demonstrated statistical trend (but not significance) towards higher apoptosis in pathological responders after neoadjuvant chemotherapy based on ATC (see Table 1). On the other hand, some researchers have shown significant correlation between low AI and better treatment outcome of BC patients [8,11]. Their results are also slightly similar to those presented by us, because in our analysis, the subgroup of women with quite good prognosis (DFS = 84.6 %) was characterized by the lowest AI.…”
Section: Discussionsupporting
confidence: 92%
“…As indicated by the present analysis (Table 2) and other studies [6][7][8][9][10][11]22], tumors with low AI are characterized by lower clinical stage and grade, slower proliferation, HR positivity, CK5/6 negativity, lower expression of TOPOIIα and P53. On the other hand, there are also some studies in which lack of correlation between apoptosis level Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The differences between African and European breast cancers have recently emerged [16,[21][22][23][24]. This study is a part of our effort to further clarifying the biology of Libyan BC and to comparing our results with the corresponding results of North European, and Central African female BC patients.…”
Section: Discussionmentioning
confidence: 96%
“…The distribution of age, axillary lymph node status, stage, histological type, and histological grades are shown in ( Table 1). Mean nuclear area, mitotic and apoptotic indices were evaluated from H & E sections as described earlier [16,17].…”
mentioning
confidence: 99%